GS&E journal > Skylight of the hotel RITZ: case study - Arnau Bover (Challenging Glass Conference, 2020)
The five-star luxury Hotel Ritz in Madrid is currently under refurbishment. The works include the construction of a new large skylight above the main hall inspired on the original design. This paper focus on the design and construction of this skylight which consist of 2 different parts, the Hall Bajo with a vault shape, and the Hall Alto which is a trapezoidal dome crowned by a pyramid roof. The structure consists in slender steel welded T profiles and small rectangular plates which connects the main beams. The connections between the structural members are welded in order to obtain a rigid connection. The perimeter consists in a welded RHS beam which creates a stiff tension ring which is completed by a visible cable. The pyramid roof performs as a compression ring for the in-plane loads and as a Vierendeel beam for the vertical loads. The cladding is composed of flat and cylindrical insulating glass panes. A geometric study is carried out in order to define the cylindrical surface that better fits a spherical frame. Some panes are structural, providing stability to the slender profiles. To guarantee the tight geometric tolerances required the structure is divided into modules, which also facilitates the transport.